New model of proliferative vitreoretinopathy in rabbit for drug delivery and pharmacodynamic studies - Sang Woong Moon; Yaoyao Sun; David Warther; Kristyn Huffman; William R. Freeman; Michael J. Sailor; Lingyun Cheng (Taylor & Francis Group, 2018)
Blinding retinal diseases become more epidemic as the population ages. These diseases, such as diabetic retinopathy and macular edema, are of chronic nature and require protracted drug presence at the disease site. A sustained intravitreal porous silicon delivery system with dexamethasone (pSiO2-COO-DEX) was evaluated in a new rabbit model of proliferative vitreoretinopathy (PVR) in a real treatment design. In contrast to the pretreatment design model, pSiO2-COO-DEX was intravitreally injected into the eyes with active inflammation. Subretinal injection of vascular endothelial growth factor (VEGF) and Matrigel induced a late-onset vitreoretinal inflammation that gradually developed into PVR. This method mimics the human disease better than PVR induced by either intravitreal cell injection or trauma. The pSiO2-COO-DEX intervened eyes had minimal PVR, while balanced saline solution or free dexamethasone intervened eyes had significantly more PVR formation. In addition, adding VEGF to the Matrigel for subretinal injection induced greater inflammation and retinal neovascularization in comparison to only Matrigel injected under the medullary ray. Clinical and pathological examinations, including fundus fluorescein angiography and optical coherence tomography, confirmed these changes. In the current study, neither subretinal injection of Matrigel or subretinal injection of VEGF and Matrigel induced choroidal neovascularization. However, the current PVR model demonstrates a chronic course with moderate severity, which may be useful for drug screening studies.